Comparative study to evaluate the effect of colloid coloading versus crystalloid coloading for prevention of spinal anaesthesia induced hypotension and effect on fetal Apgar score in patients undergoing elective lower segment caesarean section: a prospective observational study - Wani, Sadia Ali; Pandit, Basharat Hussain; Din, Mehraj Ud; Ul Nissa, Wakar; Ashraf, Asia; Bashir, Samreen; Mir, Altaf Hussain (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Spinal anesthesia for LSCS has a high incidence of maternal hypotension which can be severe and disastrous for the fetus and the mother. Coloading in these patients is a physiologically more appropriate method for preventing spinal anesthesia induced hypotension. Methods: 100 ASA I patients for elective LSCS were randomly divided into two equal groups to either receive 1000ml colloid (6% Hetastarch) or 1000ml crystalloids (Ringer lactate) as coload. NIBP, heart rate SPO2 and incidence of nausea and vomiting and use of ephedrine to treat any hypotension was recorded. Fetal outcome was measured using APGAR score at 0, 1 and 5 minutes. Results: The incidence of hypotension was lesser with colloid coload group (41.7%) as compared to the crystalloid coload group (58.3%) but the difference between the two groups was statistically insignificant. Similarly, no statistically significant difference was noted in the incidence of nausea and vomiting and Fetal APGAR score between the two groups. Conclusions: Both Colloid and Crystalloid coloading is effective in decreasing the incidence of spinal anesthesia induced hypotension during LSCS with lesser incidence of hypotension and nausea vomiting with colloid coloading.